A crustal Pb isotope map of southeastern Australia - J. Liebmann; B. Ware; D. R. Mole; C. L. Kirkland; G. Fraser; K. Waltenberg; S. Bodorkos; D. L. Huston; N. J. Evans; B. J. McDonald; K. Rankenburg; P. Datta; et al. (Scientific Data)
Abstract Lead isotopes are a powerful geochemical tracer and a popular tool applied across a broad range of scientific fields, e.g., earth sciences, archaeology, and forensic sciences. Here we present a Pb isotope dataset collected from 232 igneous samples, spanning a ca. 2.3 million km2 area in southeastern Australia, and over 3 billion years of Earth history. This contribution provides a range of isotopic maps showing the spatial variability of Pb isotopes (206Pb/204Pb, 207Pb/204Pb, and 208Pb/204Pb), magma source U/Pb and Th/U, and model ages. The samples selected for this study encompass U- and Th-poor media (i.e., K-feldspar), and U- and Th-bearing sampling media (i.e., whole-rock), providing a temporally and spatially resolved image of U and Th distribution in the crust, and their influence on crustal Pb through radiogenic ingrowth. This dataset has the potential to benefit a wide variety of different disciplines and is an important resource for addressing earth science questions ranging from unravelling crustal differentiation and architecture, through tracing magma source U- and Th-enrichment, to mineral deposit genesis.